Understanding the Causes, Consequences and Potential Solutions of Unemployment in Kashmir - Shah, Mubashir Ahmad; Dar, Mohmad Altaf (International Journal of Psychosocial Rehabilitation, 2025)
Unemployment in the state of Jammu and Kashmir is escalating at an alarming rate. The economic stress causes thousands of educated and uneducated people to join the armies of the jobless. According to a recent poll conducted by the Labor Bureau of Union Ministry, Jammu & Kashmir now has the highest unemployment rate of any state in Northern India. Based on secondary sources, this study focuses on the causes, effects, and potential solutions to the problem of unemployment in Jammu & Kashmir. The study sheds light on the state’s economic shortcomings creating an army of unemployed youth. In addition, this article examines the government’s recent initiatives to restructure the economy to reduce the rate of unemployment.